Carboxypeptidase B serves as a protective mediator in osteoarthritis - Lepus, Christin M. (2014)
OBJECTIVE: We previously demonstrated that carboxypeptidase B (CPB) protects against joint erosion in rheumatoid arthritis by inactivating complement component C5a. We also found that levels of CPB are abnormally high in the synovial fluid of individuals with another joint disease, osteoarthritis (OA). In this study, we investigated whether CPB has a role in the pathogenesis of OA. METHODS: We compared the development of OA in CPB-deficient (Cpb2(−/−)) mice and wild-type mice by subjecting them to medial meniscectomy and four months later histologically assessing cartilage damage, osteophyte formation, and synovitis in the mouse stifle joints. We measured levels of proCPB, proinflammatory cytokines, and complement components in synovial fluid samples from patients with symptomatic and radiographic knee OA. Finally, we used ELISA, flow cytometry, and hemolytic assays to assess the effect of CPB on formation of membrane attack complex (MAC)—a complement effector critical to OA pathogenesis. RESULTS: Cpb2(−/−) mice developed dramatically greater cartilage damage than wild-type mice (P<0.01) and had a greater number of osteophytes (P<0.05) and degree of synovitis (P<0.05). In synovial fluids from OA patients, high levels of proCPB were associated with high levels of proinflammatory cytokines and complement components, and levels of proCPB correlated positively with those of MAC. In in vitro complement activation assays, activated CPB suppressed the formation of MAC as well as MAC-induced hemolysis. CONCLUSIONS: Our data suggest that CPB protects against inflammatory destruction of the joints in OA, at least in part by inhibiting complement activation.